Application of co-composted biochar significantly improved plant-growth relevant physical/chemical properties of a metal contaminated soil. (March 2020) - Teodoro, Manuel; Trakal, Lukáš; Gallagher, Brett N.; Šimek, Pavel; Soudek, Petr; Pohořelý, Micheal; Beesley, Luke; Jačka, Lukáš; Kovář, Martin; Seyedsadr, Samar; Mohan, Dinesh
Abstract: A woody-biochar was added to waste biomass during a composting process. The resulting compost-char was amended to a metal contaminated soil and two plant species, L. perenne and E. sativa, were grown in a pot experiment to determine 1) plant survival and stress factors, 2) uptake of metals to plants and, 3) chemical characteristics of sampled soils and pore waters. Compost supplemented with biochar after the composting process were also tested, as well as a commercially available compost, for comparison. Co-composting with biochar hastened the composting process, resulting in a composite material of reduced odour, increased maturity, circum-neutral pH and increased moisture retention than compost (increase by 3% of easily removable water content). When amended to the soil, CaCl2 extractable and pore water metals s were reduced by all compost treatments with little influence of biochar addition at any tested dose. Plant growth success was promoted furthest by the addition of co-composted biochar to the test soil, especially in the case of E. sativa . For both tested plant species significant reductions in plant metal concentrations (e.g. 8-times for Zn) were achieved, against the control soil, by compost, regardless of biochar addition. The results of this study demonstrate that the addition of biochar into the composting process can hasten the stability of the resulting compost-char, with more favourable characteristics as a soil amendment/improver than compost alone. This appears achievable whilst also maintaining the provision of available nutrients to soils and the reduction of metal mobility, and improved conditions for plant establishment. Abstract : Highlights: Co-composting biochar with woody and green waste hastened the maturing of compost Resulting compost-char improved moisture and nutrient status when added to soil Regardless of biochar, all composts reduced CaCl2 extractable and pore water metal concentrations Plant growth success0 was promoted furthest by the addition of co-composted biochar Compost-char was shown to outperform retail purchased compost in several key soil and plant parameters Graphical abstract: Image 1